Show Posts

This section allows you to view all posts made by this member. Note that you can only see posts made in areas you currently have access to.

Messages - LLY

Pages: [1]
1
Quiz-6 / LEC5101 Quiz 6
« on: November 17, 2019, 03:39:57 AM »

\mathbf{x}^{\prime}=\left(\begin{array}{cc}{2} & {2+i} \\ {-i} & {-1-i}\end{array}\right) \mathbf{x}

\left(\begin{array}{ll}{1} & {0} \\ {0} & {1}\end{array}\right) r \xi e^{n}=\left(\begin{array}{cc}{2} & {2+i} \\ {-i} & {-1-i}\end{array}\right) \xi e^{n}

\left(\begin{array}{ll}{r} & {0} \\ {0} & {r}\end{array}\right) \xi e^{n}=\left(\begin{array}{cc}{2} & {2+i} \\ {-i} & {-1-i}\end{array}\right) \xi e^{n}

\left(\begin{array}{cc}{2-r} & {2+i} \\ {-1} & {-1-i-r}\end{array}\right)\left(\begin{array}{l}{\xi_{1}} \\ {\xi_{2}}\end{array}\right)=\left(\begin{array}{l}{0} \\ {0}\end{array}\right)

\begin{array}{cc}{2-r} & {2+i} \\ {-1} & {-1-i-r |=0} \\ {r^{2}-(1-i) r-i} & {=0} \\ {r^{2}-(1-i) r-i} & {=0} \\ {r} & {=1,-i}\end{array}

r_{1}=1 \text { and } r_{2}=-i

\text { For } r=r_{1}=1

\begin{array}{l}{\left(\begin{array}{cc}{2-1} & {2+i} \\ {-1} & {-1-i-1}\end{array}\right)\left(\begin{array}{l}{\xi_{1}} \\ {\xi_{2}}\end{array}\right)=\left(\begin{array}{l}{0} \\ {0}\end{array}\right)} \\ {\left(\begin{array}{cc}{1} & {2+i} \\ {-1} & {-(2+i)}\end{array}\right)\left(\begin{array}{l}{\xi_{1}} \\ {\xi_{2}}\end{array}\right)=\left(\begin{array}{l}{0} \\ {0}\end{array}\right)}\end{array}

\xi_{1}=-(2+i) \xi_{2}

\xi^{(1)}=\left(\begin{array}{c}{2+i} \\ {-1}\end{array}\right)

\text { for } r=r_{2}=-i

\left(\begin{array}{cc}{2-(-i)} & {2+i} \\ {-1} & {-1-i-(-i)}\end{array}\right)\left(\begin{array}{l}{\xi_{1}} \\ {\xi_{2}}\end{array}\right)=\left(\begin{array}{l}{0} \\ {0}\end{array}\right)

\left(\begin{array}{cc}{2+i} & {2+i} \\ {-1} & {-1}\end{array}\right)\left(\begin{array}{l}{\xi_{1}} \\ {\xi_{2}}\end{array}\right)=\left(\begin{array}{l}{0} \\ {0}\end{array}\right)

\xi_{1}=-\xi_{2}

\xi^{(2)}=\left(\begin{array}{c}{1} \\ {-1}\end{array}\right)

\mathbf{x}^{(1)}(t)=\left(\begin{array}{c}{2+i} \\ {-1}\end{array}\right) e^{\prime}, \mathbf{x}^{(2)}(t)=\left(\begin{array}{c}{1} \\ {-1}\end{array}\right) e^{-i t}

\begin{aligned} \mathbf{x} &=c_{1} \mathbf{x}^{(1)}(t)+c_{2} \mathbf{x}^{(2)}(t) \\ &=c_{1}\left(\begin{array}{c}{2+i} \\ {-1}\end{array}\right) e^{\prime}+c_{2}\left(\begin{array}{c}{1} \\ {-1}\end{array}\right) e^{-i t} \end{aligned}

2
Quiz-5 / TUT0301 LEC 5101 QUIZ 5
« on: November 04, 2019, 05:08:13 PM »

\begin{array}{l}{(1-t) y^{\prime \prime}+t y^{\prime}-y=2(t-1)^{2} e^{-t}, 0<t<1} \\ {y_{1}(t)=e^{t}, y_{2}(t)=t}\end{array}

(1-t) y^{\prime \prime}+t y^{\prime}-y=2(t-1)^{2} e^{-t}, 0<t<1 ; y_{1}(t)=e^{t}, y_{2}(t)=t

\left\{\begin{array}{l}{y_{1}(t)=e^{t}} \\ {y_{1}^{\prime}(t)=e^{t} \text { and }\left\{\begin{array}{l}{y_{2}(t)=t} \\ {y_{2}^{\prime}(t)=1} \\ {y_{2}^{\prime \prime}(t)=0}\end{array}\right.}\end{array}\right.

(1-t) y^{\prime \prime}+t y^{\prime}-y=0

y^{\prime \prime}+\frac{t}{1-t}-\frac{1}{1-t}=-2(t-1) e^{-t}

p(t)=\frac{t}{1-t}, q(t)=-\frac{1}{1-t}, g(t)=-2(t-1) e^{-t}

W\left[y_{1}, y_{2}\right](t)=\left|\begin{array}{ll}{y_{1}(t)} & {y_{2}(t)} \\ {y_{1}^{\prime}(t)} & {y_{2}^{\prime}(t)}\end{array}\right|=(1-t) e^{t}

Y(t)=u_{1}(t) y_{1}(t)+u_{2}(t) y_{2}(t)

\begin{aligned} u_{1}(t) &=-\int \frac{y_{2}(t) g(t)}{W\left[y_{1}, y_{2}\right](t)} d t \\ &=-\int \frac{t \cdot\left(-2(t-1) e^{-t}\right)}{(1-t) e^{t}} d t \\ &=-2 \int t e^{-2 t} d t \\ &=\left(t+\frac{1}{2}\right) e^{-2 t} \end{aligned}

\begin{aligned} u_{2}(t) &=\int \frac{y_{1}(t) g(t)}{W\left[y_{1}, y_{2}\right](t)} d t \\ &=\int \frac{e^{t} \cdot\left(-2(t-1) e^{-t}\right)}{(1-t) e^{t}} d t \\ &=2 \int e^{-t} \\ &=-2 e^{-t} \end{aligned}

Y(t)=\left(t+\frac{1}{2}\right) e^{-2 t} \cdot e^{t}+\left(-2 e^{-t}\right) \cdot t=\left(\frac{1}{2}-t\right) e^{-t}

\begin{aligned} y(t) &=y_{c}(t)+Y(t) \\ &=c_{1} e^{t}+c_{2} t+\left(\frac{1}{2}-t\right) e^{-t} \end{aligned}

3
Quiz-3 / TUT0301 QUIZ 3
« on: October 11, 2019, 03:29:46 PM »

2 y^{\prime \prime}+y^{\prime}-4 y=0, y(0)=0, y^{\prime}(0)=1

\begin{array}{l}{y=e^{r t}} \\ {y^{\prime}=r e^{n}} \\ {y^{\prime \prime}=r^{2} e^{r t}}\end{array}

\begin{array}{l}{e^{n} \neq 0} \\ {r(r+3)=0}\end{array}

r=0,-3

y=c_{1}+c_{2} e^{-3 t}

y(0)=-2

-2=c_{1}+c_{2}

y^{\prime}=-3 c_{2} e^{-3 t}

\begin{array}{l}{y^{\prime}(0)=3} \\ {3=-3 c_{2}} \\ {\text { i.e. } c_{2}=-1}\end{array}

\begin{array}{l}{\text { i.e. } c_{2}=-1} {c_{1}=-1}\end{array}

y=-1-e^{-3 t}

4
Quiz-2 / TUT 0301 QUIZ 2
« on: October 05, 2019, 10:42:06 AM »

1+\left(\frac{x}{y}-\sin (y)\right) y^{\prime}=0

\frac{\partial}{\partial y} M(x, y)=0 \quad \text { and } \quad \frac{\partial}{\partial x} N(x, y)=\frac{1}{y}

\frac{N_{x}-M_{y}}{M}=\frac{1}{y}